Sarcopenic obesity is linked to worse clinical outcomes than sarcopenia or obesity alone in hospitalized older adults - Kamile Silay; Hande Selvi Oztorun (BMC Geriatrics)
Abstract Background Sarcopenic obesity (SO), the coexistence of low muscle mass and excess fat, is increasingly recognized in older adults. Its definition and clinical implications remain debated. This study evaluated SO using the European Society for Clinical Nutrition and Metabolism–European Association for the Study of Obesity (ESPEN–EASO) criteria and examined its associations with geriatric syndromes and metabolic risk factors. Methods We conducted a retrospective cross-sectional study of 364 hospitalized patients aged ≥ 65 years who underwent bioelectrical impedance analysis. Geriatric assessments included Activities of Daily Living (ADL), Instrumental ADL (IADL), Mini Nutritional Assessment–Short Form (MNA-SF), Mini-Mental State Examination (MMSE), Geriatric Depression Scale (GDS), Clinical Frailty Scale (CFS), and handgrip strength. Mortality data were collected. Associations with SO were analyzed using univariate and multivariate logistic regression. Results SO prevalence was 24.5%. Patients with SO had worse ADL, IADL, MNA-SF scores, and lower handgrip strength (all p < 0.01). Independent predictors of SO included older age (OR = 1.064, p = 0.002), female gender (OR = 3.574, p < 0.001), hypertension (OR = 2.094, p = 0.007), and diabetes mellitus (OR = 3.342, p < 0.001). The SO group had higher mortality (15.1% vs. 9.3%, p = 0.03). A geriatric model including frailty, MNA-SF (OR = 0.472, 95% CI: 0.306–0.727), and handgrip strength (OR = 0.741, 95% CI: 0.641–0.856) showed better model fit (Nagelkerke R² = 0.474) than the metabolic model (R² = 0.223). Conclusion SO is a distinct clinical condition linked to frailty, functional decline, and mortality. Geriatric factors show stronger associations than metabolic indicators, underscoring the importance of comprehensive geriatric screening in older adults. Clinical trial registration Not applicable.